Adaptive control charts for monitoring process mean and variance - Wang, Peng Hui (2008)
The thesis is to integrate the adaptive techniques (variable sample size and/or sampling interval) in some advanced control charts and also design new adaptive control chart to improve the performance of monitoring both process mean and variance. Compared with the all-fixed charting parameters in traditional Shewhart charts, the adaptive control charts have at least one parameter to be adjusted using up-to-date process information. New adaptive charts are developed specially for different application scenarios, that is, whether variable sampling plan is feasible. The new charts are also studied for processes with autocorrelation.